2007
DOI: 10.1002/adem.200700158
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Zinc and Gadolinium on the Precipitation Sequence and Quench Sensitivity of Four Mg‐Nd‐Gd alloys

Abstract: Magnesium rare earth alloys show an excellent age hardening response, due to the decreasing solid solubility of rare earth elements with decreasing temperature-a critical requirement for age-hardening. It is known that the poor casting quality of binary Mg-Zn alloys can be improved with the addition of rare earth elements. [1] Additions of gadolinium to yttrium and neodymium-based systems have been shown to improve the mechanical properties of the alloy. [2] Previous researchers [3] showed that a 4 wt%Zn-1.5 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The XRD results, shown in Figure 2, indicate to the co-existence of Mg 24 Y 5 and Zr phase in the initial as-cast microstructural. The microstructure also contains fine dispersed Mg 12 NdY precipitates, [10,29] arrowed in Figure 1a. However, these could not be during EDS and XRD analyses.…”
Section: As-cast Microstructurementioning
confidence: 99%
See 2 more Smart Citations
“…The XRD results, shown in Figure 2, indicate to the co-existence of Mg 24 Y 5 and Zr phase in the initial as-cast microstructural. The microstructure also contains fine dispersed Mg 12 NdY precipitates, [10,29] arrowed in Figure 1a. However, these could not be during EDS and XRD analyses.…”
Section: As-cast Microstructurementioning
confidence: 99%
“…Yttrium (Y) with high solubility in magnesium is considered to be one of the most effective RE elements in improving mechanical properties of the alloys. [10,12] The corresponding fundamental literature implies that the RE-containing precipitates are highly thermally stable. [6] It is worth mentioning that the Mg-Y binary alloy exhibits poor creep and corrosion properties at high temperatures, particularly above 300°C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And in magnesium alloys, L.B. Gill found that the Mg-Nd-Gd-Zn-Zr alloys have quench sensitivity, especially when the content of element Zn is 1.3 wt% in the work [6]. D. Wu also investigated the effect of quenching rate on the microstructures and mechanical properties of the Mg-2.7Nd-0.6Zn-0.5Zr (wt.%) alloy, and found that in the air quenching sample large basal precipitates have formed in the matrix which results in low tensile strength [7].…”
Section: Introductionmentioning
confidence: 99%
“…Mg-RE alloys show good castability, high strength at elevated temperatures and good creep resistance [1][2][3][4]. Additional alloying elements in Mg-RE alloys were used to achieve higher mechanical properties [5,6]. While these systems have been extensively investigated, they are not fully understood and their potentialities have not been exhausted.…”
Section: Introductionmentioning
confidence: 99%